Social Media Marketing: Opportunities and Challenges - Singh Rana, Kulwant; Kumar, Anil (Journal of Commerce and Trade, 2016)
Consumer is the basic foundation of every business. What consumer seeks, thinks, prefers and buys is of great importance to marketers to know and study the buying behavior of people. Every person has their own taste and preferences. It is influenced by many factors. Traditionally buyers concentrate on different aspects of products like quality, price and brand preferences, but now in present time many consumers relied also on social recommendations while making purchase decision. Many consumers are using blogs/ face book reviews and ratings as mean to seek recommendation. Peer advice and find product / service information. So social media is serving as an all-purpose medium to engage with consumers at all stages of the consumer decision journey. India is in transition stage we are moving from traditional marketing tools like, TV, radio, magazine etc. to modern marketing tools i e. Social media tools face book, corporate blogs, video channels, banners as on social nets. The trend of online marketing is increasing all over the world as well as in India also. Main focus of the proposed study is to provide an understanding to the concept social media marketing and to find out the challenges and opportunities for social media marketing in India.